Leader Strategy in Improving Public Services in Tonasa 1 Sub District, Pangkep Regency - Nur, Andi Cudai; Fadillah, Hana; Sulmiah, Sulmiah (Jurnal Aktor, 2024)
This paper aims to understand the Leader's Strategy in Improving Public Services in Tonasa 1 Village. To achieve this goal, researchers use data collection techniques through observation, interviews and documentation. The data obtained from the research results were processed using qualitative analysis to find out the leader's strategy in improving public services in Tonasa Village1. The results showed that the Leader's Strategy in Improving Public Services in Tonasa 1 Village based on several indicators, namely strategy formulation and strategy implementation has been running well, but still needs to be optimized on strategy control indicators. So it can be concluded that the head of Tonasa 1 village has carried out the strategy well. This can be seen from the Strategy Formulation that has been prepared and determined always involves the Head of RW and RT in order to know what constraints occur in the community and what is desired by the community, then the implementation of the strategy, after compiling and determining the strategy then implemented, the application that has been carried out is socialization and facilitating these activities, conveying if there are activities such as socialization and serving the community well,  then strategy control, strategies that have been formulated and implemented, then strategy control where the strategy of the Head of Tonasa 1 Village in improving public services has been successful even though there are still irregularities that occur in the community but have no impact on the quality of public services